PHYSICAL CULTURE OF PERSON AND SOCIETY (Pedagogy of Higher and Secondary Education, 2006)
In the article the story goes about the problem of the down level of private needs and wishes of a person in using means of physical culture nowadays. Society’s needs, which are directed on a personality, but not on the level of his/her physical development, run out to be the motivating, factor in energization of his/her physical activity.